Human biokinetic model for soluble nickel addressing inter-individual variation. Issue 8 (10th September 2021) - Bogen, Kenneth T.; Tsuji, Joyce S.; Taylor, Michael D.; Taylor, Andrew; Patriarca, Marina
Abstract: Worker-specific Biological Exposure Action Levels (BEALs) for nickel (Ni) exposure are a urinary Ni concentration that reflects a dose that can be experienced on a daily basis without adverse systemic health effects. Several health-based reference values for systemic exposure to Ni have been derived as oral daily Ni dosing levels (e.g., 2007 WHO tolerable daily intake for Ni). To support evaluation of urinary nickel biomonitoring data in workers based on such health-based criteria, new human biokinetic models for nickel (Ni) were fit jointly to data obtained for 18 adult volunteers from four newly reported human studies and to data from two previously reported studies involving a total of 14 adult volunteers. This model and associated statistical analyses characterize and predict human Ni biokinetics after ingestion of Ni doses ≤ 20 µg/kg bw and associated inter-individual variation in urinary Ni excretion. Using this approach, we illustrate how available health-based reference values for daily Ni exposure by the oral route developed to protect against adverse health effects can be applied to derive urinary nickel BEALs for nickel workers based on their individual characteristics (e.g., shift pattern, body weight). Such worker-specific BEALs can provide health-based reference values to evaluate measures obtained through urinary Ni biomonitoring programs to complement existing industrial hygiene air monitoring programs.